Extraction of soils above concealed lithium deposits for rare metal exploration in Jiajika area: A pilot study. (August 2019) - Xu, Zhiqiang; Liang, Bin; Geng, Yan; Liu, Ting; Wang, Qiubo
Abstract: Jiajika in Sichuan, China, is an important mining area for lithium and other Group I and Group II elements. However, the weathered residual overburden makes it difficult to prospect using traditional soil geochemistry. Deep-penetrating geochemical theories provide new ideas and methods that can be used to explore for concealed ore bodies. In this study, topsoil samples were collected from 10 to 25 cm depth above two concealed lithium deposits, Vein 804 (V-804) and Vein X03 (V-X03). Lithium (Li), cesium (Cs), rubidium (Rb), beryllium (Be), and boron (B) were extracted from the soils using pure water and 0.2 mol/L potassium sulfate solutions (K2 SO4 ). Anomalies were observed for water-extractable Li, Cs, and Rb, and K2 SO4 -extractable Li, Cs, and Be in samples from above both veins. The harmonic mean of the data for each element was used to calculate the response ratio. The highest response ratios are 1.2–2.5 times and 2 to 8 times higher than the response ratios for other samples from V-804 and V-X03, respectively. Linear correlations are observed between the water-extractable and K2 SO4 -extractable elements, and imply that unbound species of the elements were extracted by K2 SO4 . The extracted elements display single peak, double peak, and multi-peak anomaly patterns, which indicate that transfer of Li, Cs, Rb, Be, and B through the overburden may be through a combination of diffusion, capillarity, electrochemical forces, and redox gradients. Graphical abstract: Image 1 Highlights: ● Extraction of Li, Cs, Rb and Be in soils using water and potassium sulfate solutions is an effective method to explore shallow buried lithium deposits in Jiajika area. ● The amount of Li, Cs, Rb, Be or B leached by K2 SO4 is highly correlated with that leached by water. ● The transfer mechanisms of elements from lithium deposits through overburden may be diffusion, capillarity, electrochemical forces and redox gradients.